2019
DOI: 10.1021/acs.joc.9b02013
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Transamidation of Secondary Amides by N–C Cleavage

Abstract: Transamidation reactions represent a fundamental chemical process involving conversion of one amide functional group into another. Herein, we report a facile, highly chemoselective method for transamidation of N-tert-butoxycarbonylation (N-Boc) activated secondary amides that proceeds under exceedingly mild conditions in the absence of any additives. Because this reaction is performed in the absence of metals, oxidants, or reductants, the reaction tolerates a large number of useful functionalities. The reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 72 publications
2
38
0
Order By: Relevance
“…In 2019, we have further extended transamidation reactions with nucleophilic amines, and reported a metal-free, highly chemoselective method for the transamidation of N-Boc-activated 2° amides under mild conditions in the absence of any additives (Scheme 10). 24 The method demonstrated excellent functional group tolerance by matching polar properties of the solvent with the stability of the ground state activated amides. The method is beneficial in terms of decreased waste generation and atom economy.…”
Section: Scheme 9 Transition-metal-free Transamidation Of Unactivatedmentioning
confidence: 99%
“…In 2019, we have further extended transamidation reactions with nucleophilic amines, and reported a metal-free, highly chemoselective method for the transamidation of N-Boc-activated 2° amides under mild conditions in the absence of any additives (Scheme 10). 24 The method demonstrated excellent functional group tolerance by matching polar properties of the solvent with the stability of the ground state activated amides. The method is beneficial in terms of decreased waste generation and atom economy.…”
Section: Scheme 9 Transition-metal-free Transamidation Of Unactivatedmentioning
confidence: 99%
“…To expand the generality of transition-metal-free transamidation of amides with nucleophilic amines, in 2019, we have disclosed an improved protocol for highly chemoselective transamidation of N-Boc-activated secondary amides (Scheme 4). [24] This method is characterized by very mild conditions, the absence of additives, and tolerance to a wide range of amides and nucleophilic amines. The synthetic utility was highlighted in the synthesis of Tigan, a commercial antiemetic, by a direct transamidation of the amide bond.…”
Section: Metal-free Transamidation Of Secondary Amidesmentioning
confidence: 99%
“…[12] Meanwhile, Verho et al [13] demonstrated that amides could be employed to accomplish metal-free transamidations in the absence of any additional reagents. Later on, Szostak [14] and Chandrasekaran [15] also achieved base-free transamidations by employing twisted N-Boc-N-phenyl-amides and N-benzyl-N-Ts-amides, respectively (Scheme 1c). Despite these progresses, challenges remain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of more general transamidation methods that proceed under base-free conditions is still in need. [16] (a) Garg and Szostak: transition metal-catalyzed transamidation [8][9] (b) Szostak: transition metal-free transamidation in the presence of base [11] (c) Verho, Szostak and Chandrasekaran: Transition metal-free and base-free transamidation [13][14][15] O (d) This work: transition metal-free and base-free transamidation of…”
Section: Introductionmentioning
confidence: 99%